Implementasi Kebijakan Plastik Berbayar di Kota Cilegon - Ismiandini, Annisa Aurellia; Yuniar, Revita; Hikmawan, M Dian (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2020)
The policy implemented by the City Government of Cilegon on Plastic is paid by the Regional Government Law No. 18 of 2008 relating to Waste Management in article 5, the Government and Regional Governments have the authority to maintain, control waste with environmental actions and insights to be in accordance with the aims and objectives of the law. Rubbish that has accumulated and is only left in the field near the yard of the residents' houses is only resolved by burning the trash, or by decomposition. This research will look at how the effectiveness and efficiency of a policy implemented by the City Government of Cilegon in finalizing the accumulation of plastic waste in the City of Cilegon by applying paid waste. By using descriptive qualitative methods, this study found that the pay plastic policy has a good impact on waste management and a positive impact on the environment.